1988
DOI: 10.1021/ie00077a008
|View full text |Cite
|
Sign up to set email alerts
|

Methyl acetate: by-product in the terephthalic acid production process. Mechanisms and rates of formation and decomposition in oxidation

Abstract: Methyl acetate is one of the main byproducts in the terephthalic acid process. This investigation has been aimed to shed more light on particular aspects concerning this byproduct: the relationship between the ester production and the process variables, methyl acetate behavior in the oxidation vessel, and recycle of the ester to the oxidation. The effect of some parameter variations on the ester formation is reported. Ester formation rate and the decomposition rate constant have been also calculated for operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 3 publications
(5 reference statements)
0
14
0
Order By: Relevance
“…The stability of FDCA was further studied in the presence of HMF because the free radicals generated by substrate oxidation might attack the product and cause it to decompose, as has been observed in solvent decomposition. 54 Thus, two reactions were carried out based on which the recovery of FDCA can be estimated. The first experiment involves the oxidation of 352 mg HMF at 180 °C and 60 bar and yielded 324 mg FDCA.…”
Section: Benchmark Of Semicontinuous Oxidation At 160 °Cmentioning
confidence: 99%
“…The stability of FDCA was further studied in the presence of HMF because the free radicals generated by substrate oxidation might attack the product and cause it to decompose, as has been observed in solvent decomposition. 54 Thus, two reactions were carried out based on which the recovery of FDCA can be estimated. The first experiment involves the oxidation of 352 mg HMF at 180 °C and 60 bar and yielded 324 mg FDCA.…”
Section: Benchmark Of Semicontinuous Oxidation At 160 °Cmentioning
confidence: 99%
“…[17] There is a close association of the rate of decomposition of the acetic acid to the rate of formation of methanol and methyl acetate. [18] The mechanisms of formation of these species are rationalized by the following set of reactions: ð2Þ ð3Þ Figure 2. Rate of reaction of dioxygen and rate of formation of carbon monoxide, carbon dioxide, and methyl 3,4-DMbenzoate.…”
Section: Some Possible Mechanisms For the Unusual Behaviormentioning
confidence: 99%
“…1.3). Roffia et al [41] studied the formation of methyl acetate and found that methyl acetate can be conveniently hydrolyzed over ion exchange catalysts, for example, to convert methyl acetate to methanol and acetic acid, which is then recycled.…”
Section: Px Oxidationmentioning
confidence: 99%